The degree to which Islamic education teachers in the northeastern Badia possess technological knowledge in light of the standards of total quality management - Aoun, Fayez Sobh Arab (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the acquisition degree of technological knowledge by Islamic education teachers in light of the total quality management (TQM) standards in the North-Eastern Badia.To achieve the objectives of the study, the researcher prepared and distributed a questionnaire to (212) male and female teachers in the schools of the directorate of education of the North-eastern Badia After conducting the statistical analysis, it was evident that the degree of possessing the technological knowledge was medium, there were statistically significant differences at the level of significance (α ≤ 0.05) between the average responses and the members of the study sample regarding the acquisition degree of technological knowledge by the Islamic education teachers in light of the TQM standards according to the variable of gender in favor of females, no statistically significant differences at the level of significance (α≥0.05) between the average responses and the members of the study sample regarding the acquisition degree of technological knowledge by the Islamic education teachers in light of the TQM standards according to the scientific qualification variable, and statistically significant differences at the level of (α≥0.05) between the average responses and the members of the study sample regarding the acquisition degree of technological knowledge by the Islamic education teachers in light of the TQM standards according to the variable of experience in favor of the number of years of experience (less than five years).